About Ritual and Word - Gómez, José María (1982)
It is presented as a novelty that a religious theme is treated and published by the Andean Rural History Seminar of the National University of San Marcos, directed by Pablo Macera. Its author, a Chilean sociologist, Pedro Morandé. It is a small mimeographed publication of 79 pages, entitled; Ritual and Word, (Approach to Latin American Popular Religiosity).